Consumer Behavior in Shopping Streets: The Importance of the Salesperson's Professional Personal Attention - Medrano, Natalia; Olarte-Pascual, Cristina; Pelegrín-Borondo, Jorge; Sierra-Murillo, Yolanda (Frontiers in Psychology, 2016)
Since the early 2010s, the emergence of a new consumer has begun. In this context, consumer behavior represents one of the greatest interests of marketing scholars and business managers due to their need to adapt their companies’ strategies to the new frontier. In order to advance understanding of this new consumer, this article focuses on analyzing consumer behavior in shopping streets. Thus, the aim of this research is to know what customers value in terms of salesperson–customer interaction quality nowadays. To achieve this, the authors conducted two studies. The results of the first study show that customers cite personal attention as the primary factor motivating their preference for small retailers in shopping streets. However, this motivation is not as relevant one for those who prefer malls. This result provides a point on which to research service quality incorporating personal attention in a second study. Using the SERVQUAL-P scale, the authors elaborate three lenses through which the quality of service from the customer’s point of view can be analyzed: normative expectations, predictive expectations, and the importance of each attribute. The most striking result is that the dimensions of expectations (normative and predictive) are the same; these results demonstrate that customers are coherent in making assessments of their expectations, evaluating service quality and satisfaction with similar criteria. However, these dimensions are different from the dimensions of importance. Our main contribution lies in the finding that personal attention, when assessed using the scale of attribute importance, is split into two dimensions: (1) courteous attention and (2) personal relationship. Courteous attention is always welcome, but personal relationships are less valued and are often even rejected. The article concludes with a discussion of the implications of these findings for marketing practices and research.